The effect of steaming time and resin content on MDF made from canola straw - Hossein Usefi (Regional Information Center for Science and Technology (RICeST), 2008)
Canola straw as a agricultural residues has been investigated for MDF production. The variables were the steaming time of 2, 5 & 8 minutes and the resin content of 9 and 11 present. Other factors being kept constant. Some of the physical and mechanical properties such as thickness swelling (TS), water absorption (WA) modulus of rupture (MOR), modulus of elasticity (MOE), internal bond (IB), were measured. In addition, canola straw fiber properties such as fiber length, diameter and cell wall thickness were determined. The results showed that the optimum condition for MDF production from canola straw is the treatment of 5 minutes steaming time and 11% resin content. All the tested mechanical and thickness swelling properties improved with the increase of steaming time level. Dimensional stability of the MDFs improved as resin content increased. WA and TS values of the produced boards were relatively high because no wax and no depithing were used during the board production. More over, the values of canola straw fiber length, diameter and cell wall thickness are 1215, 28, 7.43 micrometer respectively.